GENERATION Z AND THE UMMI METHOD: DEVELOPING QUR'AN READING SKILLS AND MODERATE CHARACTER AT WAHAS HIGH SCHOOL MADURAN - Fahimah, Siti; Luthfiyah, Lujeng (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2025)
The purpose of this study was to examine the effectiveness of the Ummi Method in enhancing the Quran reading skills of Generation Z students at SMA Wahas Maduran and in fostering a moderate religious character. This generation has grown up in a challenging digital era and often has wide access to mass media for seeking various kinds of information, including about religion. To gain an in-depth understanding of the Ummi Method’s application, this study employed a qualitative approach with a case study design. Data collection methods included observation, in-depth interviews, and document analysis. The findings indicated that the Ummi Method was effective in improving students’ comprehension and skills in reading the Quran in accordance with the rules of tajwid and makhraj. Additionally, the Ummi Method significantly contributed to shaping a moderate religious character, helping students develop attitudes of tolerance and balance in their religious practices, which are relevant to the current religious context. The success of the Ummi Method largely depended on the implementation model, which included guidance and consistent assessment from certified, professional teachers. This study recommends the broader application of the Ummi Method in educational institutions to improve Quran reading skills and foster a moderate religious character among Generation Z